Lacy reticular rash on the cheeks. An atypical presentation of erythema infectiosum. - Chuh, A.; Zawar, V. (European Journal of Pediatric Dermatology, 2006)
The facial eruption in erythema infectiosum is typically erythematous and papular, while the truncal rash is lacy, reticular, or maculopapular. We report a six-year-old Chinese boy with fever, coryzal symptoms, and facial rash, followed by eruption of truncal rash two days later. The eruption on cheeks was annular or lacy reticular in configuration, of the same morphology as the truncal rash. Parvovirus B19 DNA was detectable by PCR in the whole blood. IgM against parvovirus B19 was positive in the serum. We urge physicians to be alerted to this atypical presentation of parvovirus B19 infection.